SOLVING A SYSTEM OF SOME NON-STANDARD EQUATIONS THAT ARE NOT LINE (Archive of Conferences, 2021)
The article provides recommendations and guidelines for solving some non-linear systems ofnonlinear equations that help to expand and develop students ’thinking.